Post cholecystectomy syndrome caused by cystic duct remnant: A case report - Francino, Raíssa Paes; Marim , Kathisuemy; Oliveira , Maria Fernanda Bissa; Rossi , Maria Eduarda Almagro; Martins , Eduarda Gomes; Prado , Abraão Rodrigues Valentim do; Martins , Paula Gomes; Pagotto , Pedro Jose (Seven Editora, 2023)
CASE PRESENTATION: Patient, M.R., male, 51 years old, attended the general surgery outpatient clinic of UNESC complaining of bulging in the right inguinal region and pain on exertion with results of imaging studies suggesting the presence of cholelithiasis. Previous pathological history of laparotomy cholecystectomy 12 years ago, due to diagnosis of acute lithiasic cholecystitis. In view of the case, ultrasonography of the total abdomen was requested, which showed echogenic images with posterior acoustic leftover in the gallbladder topography. In view of the above, computed tomography of the upper abdomen was performed, which found the presence of an image compatible with a hypoplastic neogallbladder, with a thickened wall, containing a 1.5 cm calculus. From the results acquired through imaging exams, it was decided to investigate through cholangioresonance that identified filling failure measuring 1.2 cm in topography of the gallbladder next to the hepatic hilum, maintaining contact and bulging the first duodenal portion measuring 2.2 x 1.8 cm, suggesting a lithiasic biliary neovesicle. From the confirmation of the diagnosis, laparotomy cholecystectomy was indicated. Intraoperatively, an image compatible with a gallbladder of about 3 cm with thin walls and calculus inside was observed. The cystic duct, dissection of the Calot triangle without evidence of cystic artery and ligation of the remaining cystic duct were identified and repaired. The patient evolved with the usual postoperative period and after perishing all criteria was discharged. DISCUSSION: Videolaparoscopy is currently the gold standard treatment for symptomatic cases of cholelithiasis. However, some patients report the persistence or recurrence of some gastrointestinal symptoms associated with abdominal pain, which may begin 2 to 25 years after surgical intervention. These cases are described as Postcholecystectomy Syndrome (PCS). As suggested to the patient in question, once a residual calculus or neovesicle is diagnosed, surgical intervention should be performed to resolve the symptoms and avoid possible complications. FINAL CONSIDERATIONS: Patients undergoing cholecystectomy with persistence or recurrence of gastrointestinal symptoms should undergo imaging tests to rule out or confirm the diagnosis of neovesicle. DOI:https://doi.org/10.56238/innovhealthknow-011